Improving financial literacy of village community by using a saving program: A social enterprise strategy - Lani Triana Putri; Hidayatul Ihsan (Publication Division of International Ecsis Association, 2022)
A social enterprise is an organization that has a social mission and uses innovative revenue-generating techniques to fulfill their mission. Social mission in social enterprises is to improve the well-being of the community through good business practices. Nagari's Owned Enterprise (BUMNag) is an organization run with a social enterprise business model. Therefore, the establishment of BUMNag aims to gain profits through empowerment to the community. The purpose of this study is to explore how BUMNag role in improving financial literacy of village community. This research uses a qualitative approach. Data collected through observation, interviews, documentation, then analyzed data is using a modified Theory of Planned Behavior (TPB) to investigate BUMNag innovative idea of a